(untitled) (Bangladesh Veterinarian, 2013)
Peste des petits ruminants (PPR) are an acute viral disease of sheep and goats. Rapid and accurate diagnosis is essential for successful control. Reverse transcriptase polymerase chain reaction (RT-PCR), a molecular diagnostic test based on amplification of the gene target is more sensitive than other tests. The study was to find an efficient primer set and structural gene, which would be more specific and sensitive for detecting PPR virus (PPRV) in field samples. Six primer sets for six structural genes of PPR were used. Primer against NP gene (np3/np4) was specific and sensitive. To ensure efficient amplification and detection of viruses in field samples, more than one set of primers should be used and F and N gene specific primers were the most suitable. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14343 Bangl. vet. 2012. Vol. 29, No. 2, 56-62